Overview of Campylobacter in poultry, other animal species and in meat in reference to Malaysia - Abdul Aziz, Saleha (Veterinary Association Malaysia, 2003)
This paper gives an overview on the prevalence of Campylobacter in Malaysia in chickens, other food animals, some pet animals as well as in meat from several studies that were carried out over a number of years. The organisms are found to be widespread in poultry. Campylobacter jejuni is frequently isolated in poultry compared to other species. The public heath importance as well as the factors influencing colonization in chickens and contamination of chicken carcasses are briefly discussed.